2006
DOI: 10.1007/s10803-006-0149-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology in Adults with Autism and Intellectual Disability

Abstract: There have been few studies of psychopathology in adult with autism. This study examined psychiatric co-morbidity in 147 adults with intellectual disability (ID) and autism and 605 adults with ID but without autism. After controlling for the effects of gender, age, psychotropic medication and level of ID, people with autism and ID were no more likely to receive a psychiatric diagnosis than people with ID only. People with autism were less likely to receive a diagnosis of personality disorder. These findings ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(39 citation statements)
references
References 28 publications
5
34
0
Order By: Relevance
“…Lunsky et al (2009) compared patients with ASD and ID to other individuals accessing tertiary level mental healthcare in Ontario and found that individuals with ASD and ID were younger, spent more days in hospitals, and were less likely to have a psychotic disorder diagnosis than both patients with and without ID. Interestingly, fewer than half of the individuals with ASD and ID had an additional psychiatric diagnosis, although almost all (91%) were prescribed psychotropic medication, which is consistent with previous studies (Tsakanikos et al 2006(Tsakanikos et al , 2007a. Tsakanikos et al (2007b) reported that behavioral management problems predicted psychotropic medication and use of psychiatric services in adults with pervasive developmental disorder and ID.…”
Section: Mental Health Servicessupporting
confidence: 88%
See 1 more Smart Citation
“…Lunsky et al (2009) compared patients with ASD and ID to other individuals accessing tertiary level mental healthcare in Ontario and found that individuals with ASD and ID were younger, spent more days in hospitals, and were less likely to have a psychotic disorder diagnosis than both patients with and without ID. Interestingly, fewer than half of the individuals with ASD and ID had an additional psychiatric diagnosis, although almost all (91%) were prescribed psychotropic medication, which is consistent with previous studies (Tsakanikos et al 2006(Tsakanikos et al , 2007a. Tsakanikos et al (2007b) reported that behavioral management problems predicted psychotropic medication and use of psychiatric services in adults with pervasive developmental disorder and ID.…”
Section: Mental Health Servicessupporting
confidence: 88%
“…Understanding comorbid mental health problems is important not only because of the high prevalence but also because of the impact on daily functioning, long-term prognosis, and the added burden and challenges faced by individuals and their families. Individuals with ASD have higher rates of comorbidity compared to the general population (Ghaziuddin et al 1998;Moseley et al 2011), a psychiatrically referred population of youth without ASD (Joshi et al 2010), as well as individuals with ID alone (Bradley et al 2004;Brereton et al 2006;LoVullo and Matson 2009), although the latter has not been consistently found (Tsakanikos et al 2006). The most commonly reported psychiatric disorders include anxiety and depression (MacNeil et al 2009;Sterling et al 2008;White et al 2009).…”
Section: Prevalence Ratesmentioning
confidence: 99%
“…In other cases, clinicians opt to target specific interfering maladaptive behaviors or symptom clusters in the absence of a clear comorbid psychiatric diagnosis (a target-symptom approach). [146][147][148][149][150][151] Recent surveys indicate that approximately 45% of children and adolescents [152][153][154] and up to 75% of adults 8,155 with ASDs are treated with psychotropic medication. Greater age, lower adaptive skills and social competence, and higher levels of challenging behavior are associated with the likelihood of medication use.…”
Section: Psychopharmacologymentioning
confidence: 99%
“…Although a number of studies report high rates of co-morbid psychiatric disorders (e.g., depression, anxiety, etc.) in individuals with ASD (Bradley, Summers, Wood, & Bryson, 2004;de Bruin, Ferdinand, Meester, de Nijs, & Verheij, 2007;Ghaziuddin, Weidmer-Mikhail, & Ghaziuddin, 1998;Leyfer et al, 2006;Tsakanikos et al, 2006), little is known about the effects of such co-morbidity on maternal well-being. Kim, Szatmari, Bryson, Streiner, and Wilson (2000) found that mothers who had children with ASD and anxiety or depression reported greater isolation and worried more about their child's future compared to mothers who had children with ASD only.…”
mentioning
confidence: 99%